Effectiveness of probiotic Rumit in the dairy Ayrshire cattle diet - Yu. M. Smirnova; A. V. Platonov; V. A. Kotelevskaya (Аграрная наука Евро-Северо-Востока, 2023)
The effect of using enzymatic and probiotic preparation “Rumit” in feeding the Ayrshire cattle has been studied. The objectives included the analysis of biochemical blood parameters of newborn cows, research of the feed additive action on the activity of rumen microflora and milk productivity level, as well as calculation of economic efficiency of the probiotic. To implement the objectives the experiment was carried out in the period from March to July 2021 on the basis of OOO “Zarya” of Chagodoshchensky district of the Vologda Oblast. During the experiment there were formed two groups of the Ayrshire cattle of 15 cows each at the beginning of lactation, selected by the method of balanced groups. Cows of the control group received the farm diet, and the experimental group was given an additional 50 g per head per day of probiotic “Rumit” in the daily feeding. The duration of the experiment was 90 days. Use of the probiotic in the experimental group contributed to the increase of rumen microflora activity by 28 % (P≤0.05). In the analysis of biochemical blood parameters of the experimental animals, compared with the control group, there was an increase in total protein by 14.3 % (P≤0.05), urea decreased by 19 % (P≤0.05) and bilirubin fell by 21.3 % (P≤0.05). There was an increase in cows’ milk productivity in the experimental group by 6.7 % and, as a consequence, a 5.2 % reduction in the cost of energy feed units for production. Additional profit from selling milk in the experimental group was 37.32 rubles per head per day.